Return to duty/play after exertional heat injury: do we have all the answers? A lesson from two case studies. Issue 1 (December 2015) - Ketko, Itay; Druyan, Amit; Yanovich, Ran; Epstein, Yoram; Heled, Yuval
Abstract Background The common practice in the Israel defense Forces is that exertional heat related injury patients undergo a heat tolerance test 6–8 weeks post event as part of the "return to duty" process. In the case of a positive heat tolerance test the individual is classified as heat intolerant, in some cases however, the thermoregulatory recovery may be longer (several months), and therefore a second heat tolerance test is scheduled 6-8 weeks later. The presented case reports emphasize the possibility of different recovery periods of the thermoregulatory center and the distinction between congenital and acquired physiological heat intolerance. Case description Two young healthy males (A and B) were diagnosed with exertional heat related injury during a pre-recruitment sorting process. Both underwent a heat tolerance test, and were found heat intolerant. During the next months they repeated the test several times. Patient A was finally diagnosed as heat tolerant and patient B was diagnosed as heat intolerant. Conclusion Susceptibility to heat is a significant determinant for active young people such as athletes and soldiers. Both cases emphasize the importance of the heat tolerance test (and repeated test when needed) as a criteria for an exertional heat related injury patient to return to duty/play and to perform intense physical activities. These cases also emphasize the effectiveness and sensitivity of the test in identifying a temporary and a permanent state of heat intolerance.